PITA VOLUME POHON BERDIRI JENIS JATI UNTUK PENGELOLAAN HUTAN RAKYAT - Budiman Achmad; Dian Diniyati (Balai Litbang Teknologi Agroforestry, Ciamis, 2020)
The absence of an estimating tool for the volume of standing trees causes the community timber management to tend to disadvantage farmers. This study aims to provide a practical tool for estimating the volume of teak trees in an equitable timber transaction. This research used samples of 74 Nusantara Superior Teak (JUN) stands in Lemahbang Village, Bendo District, Magetan Regency, East Java, representing the smallest to largest diameter classes. The data were collected using a destructive method by felling trees and bucking them into logs at most 2 m long. The total volume of trees is obtained by summing up all the logs till the smallest diameter of 7 cm. Data were analyzed using linear regression V = a + b*DBH and non-linear V = a*DBHb. The results showed that the teak tree volume tape was better constructed using a non-linear model V = 0.0000776 DBH2.613 with r = 0.94. This teak tree volume tape can help minimize the gap in tree volume estimation between farmers and intermediaries. Besides, this volume tape can also reduce damage to other crops, minimize plant biodiversity loss, and maintain environmental quality because tree sales will tend to be selective, not clear-cut. It is also important to support the implementation of available trade by providing regulation by the local government.